Improving the Quality of Learning: An Overview of the Role of Principals' Leadership in Teacher Supervision - Sholehatun Sholehatun; Ahmad Fauzi; Abdullah Abdullah; Lu'luul Maknunah (Journal of Educational Management Research, 2024)
This study explores the role of principal leadership and teacher supervision practices in improving the quality of learning at MI Darusalam Prasi Gading Probolinggo. Through a qualitative descriptive approach, data was collected through interviews with principals, supervisors, and teachers, as well as classroom observation and documentation. The research method used is qualitative descriptive, by collecting interview, observation and documentation data and then analyzing them using triangulation of data and methods. The findings show that the principal's visionary leadership and focus on teacher professional development create a supportive and dynamic learning environment. In addition, quality teacher supervision practices, with constructive feedback and continuous professional development, make a major contribution to the improvement of teaching and learning practices in the classroom. Based on these findings, it is recommended to develop a leadership training program for school principals and increase the capacity of teacher supervision as a key step in improving the quality of learning at MI Darusalam Prasi Gading Probolinggo and encouraging the achievement of a more inclusive and meaningful learning environment for students.